PENDEKATAN NALAR BURHANI DAN PSIKOLOGI DALAM PENGEMBANGAN PENDIDIKAN ISLAM - Pustopo, Probo; Wantini (Conseils : Jurnal Bimbingan dan Konseling Islam, 2023)
Unopenness to modern science, as well as faith that restricts freedom of experimentation is one of the problems in Islamic education. To overcome this problem, one way is to strengthen the Islamic education system through a rational-psychological approach. By using a qualitative method through a literature study, it was concluded that Burhani's reasoning is considered relevant to addressing problems in Islamic education through four aspects, namely, First, maximizing the potential of reason. Second, mastery of language. Third, strengthening literacy. Fourth, independence on decision making.